Mercy, love and salvatioin in orthodox spirituality - N. Dumitrascu (Acta Theologica)
Mercy was demonstrated in the Hebrew and Greek traditions. The ideal state of Plato’s Republic exhibits mercy in a form that contrasts sharply with the Christian concept. The latter does not distinguish between those of different social conditions. In the Jewish tradition, non-observance of mercy was perceived as a transgression against a divine command which could potentially bring divine retribution on the entire community. For the Christians, mercy is not limited to members of one’s own community, but includes others, regardless of race, social class or even religion. It is a form of love which is not wasted in temporary and sentimental effusions, but actualised in concrete deeds, with the ultimate example supplied by Christ. Mercy also functions as a medicine against social inequality, serving to suppress the kinds of injustices present in every political system, as well as social solidarity. Mercy is the practical manifestation of interhuman love; it raises man from the image to the likeness of God.